Understanding the Built Form of Industrialization along the Lachine Canal in Montreal - Bliek, Desmond; Gauthier, Pierre (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2006)
This article tracks the morphogenesis of one of the birthplaces of Canadian industry: the Lachine Canal corridor in Montreal. The authors propose a reading of the evolution of the artifacts and spatial forms to be found along the canal from its construction starting in 1819. This work complements the history of Montreal's industrialization and working-class communities by offering the untold story of a piece of the city whose birth and long sedimentation of built forms testifies to the emergence, peak, and decline of a new industrial order. The urbanization of the Lachine Canal corridor is, we argue, the result of a complex dialectic between a residential spatial order of the faubourg and a first- and second-generation industrial spatial order. Accordingly, the fine folds and articulations of domestic space and the sidewalks, streets, and church steps that are the sites of socialization and exchange succeed, or have imposed upon them a divided space organized by the flows of goods, materials, and energy destined to serve the industrial machine. The urban tissues, residential and industrial, today testify through their artifacts and spatial configurations to the historical conditions that saw them created and transformed.